Environmental assessments in the Arctic Ocean. International legal obligations and gaps in existing instruments. - Sander, Gunnar (Universitetet i Tromsø, 2009)
Etter ønske fra kandidaten skal oppgaven nå publiseres i Munin. 2016-01-27 MA Environmental Assessment Environmental impact assessment (EIA) Strategic environmental assessment (SEA) Arctic governance Ocean governance Envirnmental law Law of the sea Climate change